A functional perspective on argumentation schemes - Adam Wyner (Argument & Computation, 2016)
In multi-agent systems (MAS), abstract argumentation and argumentation schemes are increasingly important. To be useful for MAS, argumentation schemes require a computational approach so that agents can use the components of a scheme to construct and present arguments and counterarguments. This paper proposes a syntactic analysis that integrates argumentation schemes with abstract argumentation. Schemes can be analysed into the roles that propositions play in each scheme and the structure of the associated propositions, yielding a greater understanding of the schemes, a uniform method of analysis, and a systematic means to relate one scheme to another. This analysis of the schemes helps to clarify what is needed to provide denotations of the terms and predicates in a semantic model.